The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.matdes.2014.11.056
|View full text |Cite
|
Sign up to set email alerts
|

The influence of particle content on the equi-biaxial fatigue behaviour of magnetorheological elastomers

Abstract: The equi-biaxial fatigue behaviour of silicone based magnetorheological elastomers (MREs) with various volume fractions of carbonyl iron particles ranging between 15% and 35% was studied. Wöhler curves for each material were derived by cycling test samples to failure over a range of stress amplitudes. Changes in complex modulus (E*) and dynamic stored energy during the fatigue process were observed. As for other elastic solids, fatigue resistance of MREs with different particle contents was shown to be depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…The material modulus rises with the increasing magnetic flux intensity until the magnetic saturation. The higher volume fraction of magnetic particles produces a higher MR effect, with an optimal volume fraction around 30% leading to the maximum of both MR effect and the long-term stability of MREs [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The material modulus rises with the increasing magnetic flux intensity until the magnetic saturation. The higher volume fraction of magnetic particles produces a higher MR effect, with an optimal volume fraction around 30% leading to the maximum of both MR effect and the long-term stability of MREs [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Equi-biaxial fatigue tests of MRE samples with a range of magnetic particle contents in the presence of a magnetic field further strengthened Table 3). When compared with previous results without magnetic fields (Zhou et al, 2015), it was found that E* at failure for MREs with various particle content were slightly higher in the presence of magnetic fields, but this was in a relatively small range. The instantaneous increase in modulus experienced by an MRE when a magnetic field is applied is well known and has been researched extensively.…”
Section: Modulus (E*)mentioning
confidence: 54%
“…A limiting value of E* at failure was reached for each material and the values of E* at failure were within a quite small range when the samples were tested both with and without a magnetic field. As previously found (Zhou et al, 2015), dynamic stored energy can also be used as a plausible predictor in determining the fatigue life of MREs when they are subjected to external magnetic fields. However, the magnetic field did not have a significant influence on the damping loss factor for the range of MREs tested.…”
Section: Damping Loss Factor (η)mentioning
confidence: 79%
“…Considering this, by employing the dynamic bubble inflation testing system developed in the Centre for Elastomer Research in the Dublin Institute of Technology [21], equi-biaxial fatigue behaviour of MREs was investigated by using engineering stress as the control mode. Previous studies [22,23] have shown that stored energy density can be used as a reliable fatigue life predictor for silicone based MREs. In this paper, commonly used fatigue life predictors for elastomers including maximum stress, maximum strain and strain energy density were investigated thoroughly with the aim of determining suitable fatigue life predictors for MREs and developing general equations for the fatigue life prediction of MREs.…”
Section: Introductionmentioning
confidence: 99%